The Influence of Prices and Promotions on Interest in Buying Electric Bikes in Telering Jatiwangi, Jatiwangi Subdistrict, Majalengka District - Gita Kartika Sari; Tia Aprilia Susnita; Risa Rifianti Utami (Politeknik Mardira Indonesia, 2024)
Telering Jatiwangi Majalengka located at Jl. Ahmad Yani No.48 Sutawangi, Jatiwangi District, Majalengka Regency, West Java, has been since December 2012. The establishment of Telering Jatiwangi aims not only to meet consumer needs but also to maximize profits. To achieve these objectives, it is essential to market product at affordable prices and implement effective promotional strategies to attract costumers to purchase Electric Bicycles at Telering Jatiwangi. The purpose of this study is to examine the effects of priceand promotion on the interest in buying Electric Bicycles at Telering Jatiwangi, Jatiwangi District, Majalengka Regency. The research employs a quantitative approach with both descriptive and verifiable analysis. The findings reveal that the multiple correlation coefficient (simultaneous) is 0.844, indicating a very strong relationship between price, promotion and buying interest. Furthermore, the analysis shows that price and promotion exert a positive and significant influence on buying interest, with an F value of 98.738 > 3.11 and a significance value of < 0.05, which is 0.000 < 0.05. This suggests that as price and promotion improve, so does the buying interest at Telering Jatiwangi, Majalengka Regency. Overall, it can be concluded that the variable of price and promotion can be effectively combined to measure buying interest.